2014
DOI: 10.1063/1.4895116
|View full text |Cite
|
Sign up to set email alerts
|

GaAs1−y−zPyBiz, an alternative reduced band gap alloy system lattice-matched to GaAs

Abstract: The growth and properties of alloys in the alternative quaternary alloy system GaAs1−y−zPyBiz were explored. This materials system allows simultaneous and independent tuning of lattice constant and band gap energy, Eg, over a wide range for potential near- and mid-infrared optoelectronic applications by adjusting y and z in GaAs1−y−zPyBiz. Highly tensile-strained, pseudomorphic films of GaAs1−yPy with a lattice mismatch strain of ∼1.2% served as the host for the subsequent addition of Bi. Lattice-matched alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
4
18
0
Order By: Relevance
“…This enhanced incorporation of P at low temperatures suggests the feasibility of applying PH 3 for the low temperature growth of GaAs 1-y P y as well as other P-containing quaternary alloy systems, such as GaAs 1-x-y P x Bi y . 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhanced incorporation of P at low temperatures suggests the feasibility of applying PH 3 for the low temperature growth of GaAs 1-y P y as well as other P-containing quaternary alloy systems, such as GaAs 1-x-y P x Bi y . 22 …”
Section: Discussionmentioning
confidence: 99%
“…High temperature growth of these alloys often leads to phase separation as predicted by the equilibrium phase diagrams. The recent investigation of phosphorous containing metastable quaternary alloys, such as GaAs 1-x-y P x Bi y , 22 also requires low growth temperatures. Low growth temperatures are also known to extend the pseudomorphic limit by suppressing thermally-activated dislocation nucleation and glide.…”
mentioning
confidence: 99%
“…However, while no GaBi x As 1−x QW lasers have yet been developed with sufficiently high Bi compositions to suppress the dominant CHSH Auger recombination mechanism, progress in developing dilute bismide QW lasers has been rapid and efforts to reach this important milestone are ongoing. For example, recent investigations of GaBi x P y As 1−x−y alloys have shown that incorporation of a small amount of phosphorus (P) enhances Bi incorporation during MOVPE growth [30], while also providing the possibility to grow dilute bismide laser structures which are lattice-matched to GaAs. Although it is likely to be related to the P-induced reduction of compressive strain in the quaternary alloy, the precise mechanism by which co-alloying P and Bi enhances Bi incorporation has yet to be determined.…”
Section: Devicesmentioning
confidence: 99%
“…In most cases, experimental probes are far larger than the dimensions of the droplets/tracks on the surface (order of nm to μ m7891011171934), with measurements unavoidably recording an unresolved average of the entire probed area. While the removal of Bi surface droplets post growth (through selective wet chemical etching), and prior to characterisation, appears to rid the Bi metal, a number of experimental studies383940 have neglected to consider their lasting impact on the structural and optical properties of the epitaxial surface. This issue we investigate in the present study using electron microscopy techniques and micro-optical probes (lateral resolution ~1 μ m).…”
mentioning
confidence: 99%